Effect of Led Light Intensity on Survival Rate and Growth Rate of Cantang Grouper - Putrawan, Putu Herdi; Prasetia, I Nyoman Dodik; Setiabudi, Gede Iwan (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 2 (2022): ATBES, 2022)
This study aimed to examine the effect of the intensity of LED light on the survival rate of Cantang grouper larva in indoor cultivation, and the intensity of LED light on the growth rate of Cantang grouper larva in indoor cultivation. This research is an experimental research type. The subjects in this study were Cantang grouper larva in Penyabangan Village, Buleleng Regency using microscopic observations which were analyzed descriptively and recorded in the table. The data analysis technique used in this study uses SPSS Windows version 21 by using the normality test, the Kruskal walls test and the post hoc test. The results of this study indicate that the intensity of LED light affects the survival rate, this can be seen from Pool 3 filled with 2,000 LUV LEDs which has the highest SR level, which is 5%. The intensity of the LED light affects the growth of the larva studied by using the parameters of length and the percentage of feed consumed in the larva's stomach. This is indicated by the length and the highest percentage of fish larva belly in pond 3 which was treated with 2,000 LUX LED.